Hereditary Hemorrhagic Telangiectasias Osler – Weber Rendu Syndrome - Khan, Akram (International Journal of Research in Medical Surgical Nursing, 2025)
Hereditary Haemorrhagic Telangiectasias (HHT) is a genetic autosomal Dominant blood vessel disorder characterized by mucocutaneous Telangiectasias due to arteriovenous malformation (AVMs). The Hereditary Hemorrhagic Telangiectasias Manifested by severe epistaxis, red or purplish pinhead spots over the skin (Telangiectasias), and arteriovenous malformation (AVMs) of the Lungs, Brain, and GIT. Diagnosis of HHT include HHT severity score and various radiological studies to find out the AVMs. Management of HHT is to reduce acute blood loss and maintain target hemoglobin level, in advance stage of disease oral and intravenous administration of tranexamic acid and Bevacizumab. Surgical management including embolization of blood vessel, septal dermoplasty and young's nasal closure procedure.